THEME: THE HISTORY OF THE FORMATION AND DEVELOPMENT OF THE METHODS OF THE PHYSICAL DEVELOPMENT OF CHILDREN IN SENIOR PRESCHOOL AGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article contains information about the physical development of senior preschool children. There are also opinions of scientists on the physical development of children are considered in this article.